U.P. College Baguio (1972-1977) systems analysis of institutional changes - Queano, Bella Lagera 1947- (1978)
The College operated with no clear and approved organizational chart except for those arbitrarily prepared by past administrators, resulting in confused lines of communication and functional authority, and creating much disequilibrium in the system. Curriculum adaptations consisted in the shift from mere divisional to interdivisional curriculum, the institution of new courses and degree programs, and the elevation of courses to higher status as a way of strengthening the Divisional Course designs. Faculty turnover, the failure of fellows to return from fellowship grants, loss of faculty due to the imposition of martial law in 1972 resulted in the hiring of lectureres, estabilishment of consortia with other institutions of learning in the city, cross-teaching of faculty in the different divisions, and faculty overloading. The students and graduates stay mainly for the General Education program indicating the College's failure to serve the needs of the Northern Region.
Appendices: leaves 131-161
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: University of the Philippines, Baguio City; School management and organization -- Philippines; Universities and colleges -- Philippines -- Baguio